Iridium oxide-doped diamond double-layer electrode and preparation method and application thereof
By introducing doped diamond particles into the iridium oxide film layer to form an iridium oxide-doped diamond double-film electrode, the problems of poor conductivity of the doped diamond electrode and uneven coverage during the preparation process are solved, and efficient electrocatalytic degradation performance and excellent conductivity are achieved.
Patent Information
- Application Number
- CN202211070903.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-09-02
AI Technical Summary
The existing doped diamond electrodes have poor conductivity, resulting in low efficiency and high energy consumption. At the same time, the problem of uneven coverage or even falling off is prone to occur during the preparation process.
Iridium oxide-doped diamond double-film electrode is used to introduce doped diamond particles into the iridium oxide film layer to form a heterojunction to improve conductivity, and to improve binding force and catalytic performance by controlling the thickness of the double-layer film and the concentration of doped elements.
The film layer coverage is achieved, the electrocatalytic degradation and conductivity are improved, and the problems of poor conductivity and uneven coverage during the preparation process are solved.
Abstract
Description
Technical Field
[0001] The invention discloses an iridium oxide-doped diamond double-film electrode and a preparation method and application thereof, belonging to the technical field of electrode preparation. Background Art
[0002] Doped diamond has a very wide electrochemical window, a very high oxygen evolution potential, a very low background current, excellent chemical stability, surface inertness and weak adsorption, and is a research hotspot in the field of environmental electrochemistry. In the field of ecological environment, it is often used to treat difficult-to-biodegrade organic wastewater with high concentration, high salinity, high ammonia nitrogen, strong acidity and alkalinity, and is called the "ideal anode material."
[0003] Electrocatalytic oxidation is known as an "environmentally friendly" technology. It uses electrons as catalysts and can effectively treat wastewater containing organic pollutants at room temperature and pressure. With the continuous industrialization of electrocatalytic oxidation, it is becoming possible to apply electrocatalytic oxidation technology to large-scale field applications. The most critical thing in electrocatalytic oxidation is the selection of anode materials. Iridium oxide has good electrocatalytic oxidation properties and has a good oxidative degradation effect on the treatment of organic wastewater. However, due to its low oxygen evolution potential, it cannot oxidize difficult-to-degrade organic matter with high potential.
[0004] However, although the doped diamond electrode has an extremely high oxygen evolution potential, its conductivity is poorer than that of metal or oxide films, and there are problems such as low efficiency and high energy consumption during use. In addition, under the existing process technology, the doped diamond electrode based on foam or particles is prone to uneven coverage or even falling off during the preparation process. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide an iridium oxide-doped diamond double-film electrode with uniform film coverage, excellent electrical conductivity and electrocatalytic degradation performance.
[0006] The second object of the present invention is to provide a method for preparing an iridium oxide-doped diamond double-layer electrode.
[0007] The third object of the present invention is to provide an application of an iridium oxide-doped diamond double-film electrode.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The invention discloses an iridium oxide-doped diamond double-film electrode, which comprises a substrate and an electrode working layer arranged on the surface of the substrate, wherein the electrode working layer is composed of an iridium oxide film layer and a doped diamond film layer, and the iridium oxide film layer is composed of an iridium oxide matrix and doped diamond particles uniformly dispersed in the iridium oxide matrix.
[0010] The inventor unexpectedly discovered that the iridium oxide film layer has excellent electrical conductivity, but due to its low oxygen evolution potential, it cannot oxidize difficult-to-degrade organic matter with high oxidation potential, while the doped diamond electrode has an extremely high oxygen evolution potential, but poor electrical conductivity. However, when the two are composited, the iridium oxide film layer and the doped diamond double film layer form a heterojunction, thereby strengthening the electron separation in a constant electric field and thus improving the current efficiency, thereby obtaining a composite electrode with the most excellent catalytic performance.
[0011] In addition, the introduction of doped diamond particles into the iridium oxide film layer can, on the one hand, improve the problem of thermal expansion coefficient mismatch between the double-layer films, and on the other hand, easily form OC bonds with the doped diamond film layer. Through the above two effects, the double-layer film not only has excellent bonding performance, but also further improves the conductivity. In addition, it can also be used as the crystal nucleus for the subsequent CVD preparation of the doped diamond film layer to improve the bonding force between the double-layer films.
[0012] In a preferred embodiment, the substrate is selected from one of the metals nickel, niobium, tantalum, zirconium, copper, titanium, cobalt, tungsten, molybdenum, chromium, iron or one of their alloys; or the substrate is selected from one of the ceramics Al2O3, ZrO2, SiC, Si3N4, BN, B4C, AlN, TiB2, TiN, WC, Cr7C3, Ti2GeC, Ti2AlC and Ti2AlN, Ti3SiC2, Ti3GeC2, Ti3AlC2, Ti4AlC3, BaPO3 or their doped ceramics; or the substrate is selected from one of the composite materials composed of the above-mentioned metals and ceramics, or the substrate is selected from diamond or Si; preferably ceramics.
[0013] The base shape includes at least one of powder, granular, cylindrical, cylindrical, and flat plate;
[0014] The substrate structure is selected from at least one of a three-dimensional continuous network structure, a two-dimensional continuous mesh structure and a two-dimensional closed flat plate structure.
[0015] In a preferred solution, the thickness of the iridium oxide film layer is 10-120 μm, the thickness of the doped diamond film layer is 5-20 μm; the particle size of the doped diamond particles is 0.1-20 μm, preferably 15-20 μm.
[0016] The inventors found that controlling the thickness of the iridium oxide film layer and the doped diamond film layer within the above range makes it easier to form OC bonds and intermediates, thereby improving the bonding strength of the two films. In addition, under the coordination of the above thicknesses, the conductive performance of the final coupled electrode is optimal.
[0017] In a preferred solution, the volume fraction of the doped diamond particles in the iridium oxide film layer is 0.1%-20%.
[0018] In a preferred embodiment, the iridium oxide film matrix is further doped with boron, and the molar ratio of iridium to boron is 1:1-3.
[0019] The inventors found that the iridium oxide film layer is doped with boron. The incorporation of B atoms can increase the Ir 3+ The local concentration of iridium and oxygen atoms increases, causing atomic rearrangement, which further improves the dispersion of iridium and oxygen atoms, thereby changing the microstructure of the unit cell. The improvement of the microstructure can increase the catalytic active sites, while improving the mass transfer performance, increasing the binding force, and increasing the oxygen evolution potential.
[0020] In a preferred embodiment, the doping element in the doped diamond film layer is selected from at least one of boron, nitrogen, phosphorus and lithium, preferably boron; and the doping method includes one or more combinations of constant doping, multi-layer variable doping and gradient doping.
[0021] In a preferred embodiment, the mass fraction of the doping element in the doped diamond film layer is 2‰-10‰.
[0022] The inventors found that the doping elements can react with the metal elements in the oxide coating to generate intermediate products, thereby further improving the bonding strength between the double-layer films.
[0023] In a preferred embodiment, the doped diamond film layer forms a full coating, a half coating, or a selective coating on the surface of the iridium oxide film layer, preferably a full coating.
[0024] In a preferred embodiment, the doping element in the doped diamond particles is selected from at least one of boron, nitrogen, phosphorus and lithium, preferably boron; and the doping method includes one or more combinations of constant doping, multi-layer variable doping and gradient doping.
[0025] In a preferred embodiment, the mass fraction of the doping element in the doped diamond particles is 2‰-10‰.
[0026] In a preferred embodiment, the iridium oxide-doped diamond double-film electrode comprises a substrate and an electrode working layer arranged on the surface of the substrate, and the electrode working layer is a double-layer film structure, which comprises, from bottom to top, an iridium oxide film layer and a doped diamond film layer.
[0027] In a preferred embodiment, the iridium oxide-doped diamond double-film electrode comprises a substrate and an electrode working layer arranged on the surface of the substrate, wherein the electrode working layer is a double-layer film structure, which comprises, from bottom to top, a doped diamond film layer and an iridium oxide film layer.
[0028] The invention discloses a method for preparing an iridium oxide-doped diamond double-film electrode. The method comprises the following steps: firstly preparing an iridium oxide film layer on a substrate surface by an electro-deposition method, and then preparing a doped diamond film layer by chemical vapor deposition.
[0029] The preferred solution is that the process of preparing the iridium oxide film layer by the electrodeposition method is as follows: dissolving an iridium source in an acid, adjusting the pH value to 9 to 11 to obtain a deposition solution, adding boric acid to the deposition solution to obtain a mixed solution, adding doped diamond particles to the mixed solution to obtain an electrolyte, aging and hydrolyzing the electrolyte, and then using the substrate as an anode to perform cyclic voltammetry electrodeposition to obtain the iridium oxide film layer.
[0030] Further preferably, the iridium source is selected from at least one of IrCl3, K2IrCl6, K3IrCl6, IrCl4, and H2IrCl6.
[0031] More preferably, the acid is selected from oxalic acid, hydrochloric acid and nitric acid.
[0032] Further preferably, at least one of potassium carbonate, potassium bicarbonate and potassium hydroxide is used to adjust the pH value to 9-11.
[0033] Further preferably, in the deposition solution, the molar ratio of iridium to hydrogen ions is (0.5-4):10.
[0034] Further preferably, in the mixed solution, the mass ratio of the iridium source to the boric acid is 1 g:4-50 mg.
[0035] Further preferably, the mass ratio of the doped diamond particles to the mixed liquid is 0.05-100:1000.
[0036] Further preferably, the electrolyte aging and hydrolysis time is ≧1h.
[0037] More preferably, the electrodeposition time is 0.5-2h.
[0038] Further preferably, during cyclic voltammetry electrodeposition, a graphite electrode or a Ti electrode is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode.
[0039] Further preferably, the parameters of the cyclic voltammetry electrodeposition are: the lower voltage limit is -1.5 to 0.2 V, the upper voltage limit is 0 to 1.8 V, the scan rate is 5 to 500 mV / s, and the number of scan cycles is 10 to 500 r.
[0040] The preferred scheme is that the process of preparing the doped diamond film layer by chemical vapor deposition is as follows: placing the obtained substrate material in a chemical deposition furnace, the mass flow ratio of the introduced gas is hydrogen: methane: doping gas source = 100: (1-5): (01.-2.5), the growth pressure is 2-5Kpa, the growth temperature is 600-950°C, the number of growths is 1-4 times, and after each growth, the substrate is taken out, the positive and negative sides are replaced, and then the growth is continued. The single growth time is 1-20h, and the doping gas source is selected from at least one of ammonia, phosphine, and borane.
[0041] The invention discloses a method for preparing an iridium oxide-doped diamond double-film electrode, which comprises the following steps: firstly planting nano-diamond seed crystals on the surface of a substrate, then preparing a doped diamond film layer on the surface of the substrate planted with the nano-diamond seed crystals by chemical vapor deposition, and finally preparing an iridium oxide film layer on the surface of the substrate containing the doped diamond film layer by electrodeposition.
[0042] In a preferred embodiment, the substrate is firstly ultrasonically cleaned.
[0043] In a preferred embodiment, the process of planting nano-diamond seed crystals on the surface of the substrate is as follows: the substrate containing the ruthenium oxide active film layer is vertically suspended and immersed in a suspension containing nano-diamond seed crystals, ultrasonically vibrated for ≥15 minutes, and finally cleaned and dried with alcohol. The particle size of the nano-diamond seed crystals is 5-20nm, and the mass concentration of the nano-diamond seed crystals in the suspension is 1-5%.
[0044] The inventors have found that nano-diamond seed crystals are conducive to the uniform deposition of doped diamond film layers. Of course, the particle size and mass concentration of the nano-diamond seed crystals need to be effectively controlled. If the seed crystal size is small, the particles are easy to agglomerate; if the seed crystal size is large, the film bonding force is not strong; if the mass concentration is too high, the nano-seed crystals will agglomerate; if the mass concentration is too low, it will not provide enough nucleation sites for diamond growth.
[0045] The preferred solution is that the process of preparing the doped diamond film layer by chemical vapor deposition is as follows: placing a substrate planted with nano-diamond seed crystals in a chemical deposition furnace, the mass flow ratio of the introduced gas is hydrogen: methane: doping gas source = 97: (1-5): (01.-2.5), the growth pressure is 2-5Kpa, the growth temperature is 600-950°C, the number of growths is 1-4 times, and after each growth, the substrate is taken out, the positive and negative sides are replaced, and then the growth is continued. The single growth time is 1-20h, and the doping gas source is selected from at least one of ammonia, phosphine, and borane.
[0046] The preferred solution is that the process of preparing the iridium oxide film layer by the electrodeposition method is as follows: dissolving an iridium source in an acid, adjusting the pH value to 9 to 11 to obtain a deposition solution, adding boric acid to the deposition solution to obtain a mixed solution, adding doped diamond particles to the mixed solution to obtain an electrolyte, aging and hydrolyzing the electrolyte, and then using the substrate as an anode to perform cyclic voltammetry electrodeposition to obtain the iridium oxide film layer.
[0047] Further preferably, the iridium source is selected from at least one of IrCl3 / K2IrCl6 / K3IrCl6 / IrCl4 / H2IrCl6.
[0048] More preferably, the acid is selected from oxalic acid, hydrochloric acid and nitric acid.
[0049] More preferably, at least one of potassium carbonate, potassium bicarbonate and potassium hydroxide is used to adjust the pH value to 9-11.
[0050] Further preferably, in the deposition solution, the molar ratio of iridium to hydrogen ions is (0.5-4):10.
[0051] Further preferably, in the mixed solution, the mass ratio of the iridium source to the boric acid is 1 g:4-50 mg.
[0052] Further preferably, the mass ratio of the doped diamond particles to the mixed liquid is 0.05-100:1000.
[0053] Further preferably, the electrolyte aging and hydrolysis time is ≧1h.
[0054] More preferably, the electrodeposition time is 0.5-2h.
[0055] Further preferably, during cyclic voltammetry electrodeposition, a graphite electrode or a Ti electrode is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode.
[0056] Further preferably, the parameters of the cyclic voltammetry electrodeposition are: the lower voltage limit is -1.5 to 0.2 V, the upper voltage limit is 0 to 1.8 V, the scan rate is 5 to 500 mV / s, and the number of scan cycles is 10 to 500 r.
[0057] The invention discloses an application of an iridium oxide-doped diamond double-film electrode. The doped diamond-iridium oxide coupling electrode is applied to the fields of electrochemical synthesis, electrochemical sewage purification, electrochemical detection and electrochemical biosensor.
[0058] Beneficial Effects
[0059] The invention provides an iridium oxide-doped diamond double-film electrode. The electrode working layer of the doped diamond-iridium oxide coupling electrode consists of an iridium oxide film layer and a doped diamond film layer. The iridium oxide film layer consists of an iridium oxide matrix and doped diamond particles uniformly dispersed in the iridium oxide matrix.
[0060] The inventor unexpectedly discovered that the iridium oxide film layer has excellent electrical conductivity, but due to its low oxygen evolution potential, it cannot oxidize difficult-to-degrade organic matter with high oxidation potential, while the doped diamond electrode has an extremely high oxygen evolution potential, but poor electrical conductivity. However, when the two are composited, the iridium oxide film layer and the doped diamond double film layer form a heterojunction, thereby strengthening the electron separation in a constant electric field and thus improving the current efficiency, thereby obtaining a composite electrode with the most excellent catalytic performance.
[0061] In addition, the introduction of doped diamond particles into the iridium oxide film layer can, on the one hand, improve the problem of thermal expansion coefficient mismatch between the double-layer films, and on the other hand, easily form OC bonds with the doped diamond film layer. Through the above two effects, the double-layer film not only has excellent bonding performance, but also further improves the conductivity. In addition, it can also be used as the crystal nucleus for the subsequent CVD preparation of the doped diamond film layer to improve the bonding force between the double-layer films. DETAILED DESCRIPTION
[0062] Example 1
[0063] Silicon carbide is used as a substrate, the substrate is ultrasonically cleaned, and an iridium oxide film layer is prepared by an electrodeposition method. The specific process is: 10g K2IrCl6 is dissolved in oxalic acid, potassium hydroxide is used to adjust the pH value to 10 to obtain a deposition solution, 500mg boric acid is added to the deposition solution to obtain a mixed solution, and then boron-doped diamond particles with a particle size of 5μm are added to the mixed solution, wherein the boron doping concentration is 5%, and the mass ratio of the boron-doped diamond particles to the solution is 5:1000 to obtain an electrolyte, the electrolyte is aged and hydrolyzed for 2h, and then the silicon carbide substrate is used as an anode to perform cyclic voltammetry electrodeposition to obtain an iridium oxide film layer; the electrodeposition time is 2h; during the cyclic voltammetry electrodeposition, a graphite electrode is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode; the parameters of the cyclic voltammetry electrodeposition are: a voltage lower limit of -1.0V, a voltage upper limit of 1.5V, a scanning rate of 200mV / s, and a scanning circle number of 200r.
[0064] A substrate containing an iridium oxide active film layer is placed in a chemical vapor deposition furnace: the mass flow ratio of the introduced gas is hydrogen: methane: doping gas source = 100:3:0.6, the growth pressure is 3Kpa, the growth temperature is 800°C, the number of growths is 4 times, and after each growth, the substrate is taken out, replaced with the front and back sides, and then the growth is continued. The single growth time is 12 hours, and the doping gas source is selected from borane.
[0065] The iridium oxide-doped diamond double-layer film electrode prepared in the above Example 1 has a thickness of 90 μm for the iridium oxide film layer, a thickness of 15 μm for the doped diamond film layer, and a molar ratio of iridium element to boron element in the iridium oxide film of about 1:1.46. The obtained iridium oxide-doped diamond film layer is firm and does not fall off when scratched. The volume fraction of the doped diamond particles in the ruthenium oxide film layer is 10%.
[0066] The prepared boron-doped diamond-ruthenium oxide coupling electrode was encapsulated, and a stainless steel electrode was used as the negative electrode. 1L of active orange X-GN simulated dye wastewater with an initial concentration of 100mg / L and an electrolyte Na2SO4 concentration of 0.1mol / L was prepared. The Ph of the solution was adjusted to 3 with sulfuric acid, and the solution was placed on a magnetic stirrer with a speed of 200r / min to maintain a current density of 100mA / cm during the degradation process.2 After 2 hours of degradation, the chromaticity removal rate of the dye reached 99%, and the degradation was basically complete.
[0067] Example 2
[0068] Silicon carbide is used as a substrate, and the substrate is ultrasonically cleaned. A doped diamond film layer is prepared by a chemical vapor deposition method. The specific process is: the substrate is vertically suspended and immersed in a suspension containing nano-diamond seed crystals, ultrasonically vibrated for 30 minutes, and cleaned and dried with alcohol to obtain a substrate planted with nano-diamond seed crystals. The particle size of the nano-diamond seed crystals is 5nm, and the mass concentration of the nano-diamond seed crystals in the suspension is 5%; the substrate planted with the nano-seed crystals is placed in a chemical vapor deposition furnace: the mass flow ratio of the introduced gas is hydrogen: methane: doping gas source = 100: 4: 0.8, the growth pressure is 3Kpa, the growth temperature is 850°C, the growth number is 4 times, and each time the substrate is grown, the substrate is taken out, and the positive and negative sides are replaced, and then the growth is continued. The single growth time is 12 hours, and the doping gas source is selected from borane;
[0069] An iridium oxide film layer is deposited on a substrate containing a doped diamond film layer, and the iridium oxide film layer is prepared by an electrodeposition method. The specific process is as follows: 10g K2IrCl6 is dissolved in acid, and then the pH value is adjusted to 10 to obtain a deposition solution, 400mg boric acid is added to the deposition solution to obtain a mixed solution, and then boron-doped diamond particles with a particle size of 2μm are added to the mixed solution, wherein the boron doping concentration is 5%, and the mass ratio of the boron-doped diamond particles to the solution is 10:1000 to obtain an electrolyte, the electrolyte is aged and hydrolyzed for 2h, and then a silicon carbide substrate is used as an anode to perform cyclic voltammetry electrodeposition to obtain an iridium oxide film layer; the electrodeposition time is 2h; during the cyclic voltammetry electrodeposition, a graphite electrode is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode; the parameters of the cyclic voltammetry electrodeposition are: a voltage lower limit of -1.0V, a voltage upper limit of 1.5V, a scanning rate of 200mV / s, and a scanning circle number of 200r.
[0070] The iridium oxide-doped diamond double-layer film electrode prepared in the above Example 2 has a thickness of 98 μm for the iridium oxide film layer, a thickness of 17 μm for the doped diamond film layer, and a molar ratio of iridium element to boron element in the iridium oxide film of about 1:1.38. The obtained iridium oxide-doped diamond film layer is firm and does not fall off when scratched. The volume fraction of the doped diamond particles in the ruthenium oxide film layer is 20%.
[0071] The prepared boron-doped diamond-ruthenium oxide coupling electrode was encapsulated, and a stainless steel electrode was used as the negative electrode. 1L of active orange X-GN simulated dye wastewater with an initial concentration of 100mg / L and an electrolyte Na2SO4 concentration of 0.1mol / L was prepared. The Ph of the solution was adjusted to 3 with sulfuric acid, and the solution was placed on a magnetic stirrer with a speed of 200r / min to maintain a current density of 100mA / cm during the degradation process. 2 After 2 hours of degradation, the chromaticity removal rate of the dye reached 97%, and the degradation was basically complete.
[0072] Comparative Example 1
[0073] The other conditions were the same as those in Example 1, except that boric acid was not added when the iridium oxide film was prepared by the electrodeposition method. After chemical vapor deposition coating, the obtained doped diamond film had obvious shedding, and the degradation effect was far inferior to that in Example 1.
[0074] Comparative Example 2
[0075] The other conditions were the same as those in Example 1, except that no doped diamond particles were added when the iridium oxide active film layer was prepared by the electrodeposition method. After chemical vapor deposition coating, the obtained doped diamond film layer fell off when scratched, the film layer had insufficient bonding strength, the heterojunction effect was poor, and the degradation effect was far inferior to that in Example 1.
[0076] Comparative Example 3
[0077] The other conditions are the same as those in Example 2, except that when the doped diamond film is prepared by chemical vapor deposition, the growth times are 10 times and the thickness of the obtained doped diamond film is 37 μm. After the iridium oxide film is prepared by electrolysis, the thickness of the obtained ruthenium oxide active film layer is 5 μm. The bonding force between the double-layer films is insufficient, the heterojunction effect is poor, and the degradation effect is far inferior to that in Example 2.
Claims
1. An iridium oxide-doped diamond double-layer electrode, characterized in that: The doped diamond-iridium oxide double-film electrode comprises a substrate and an electrode working layer arranged on the surface of the substrate, wherein the electrode working layer is composed of an iridium oxide film layer and a doped diamond film layer, wherein the iridium oxide film layer is composed of an iridium oxide matrix and doped diamond particles uniformly dispersed in the iridium oxide matrix; the thickness of the iridium oxide film layer is 10-120 μm, the thickness of the doped diamond film layer is 5-20 μm; and the particle size of the doped diamond particles is 0.1-20 μm; The iridium oxide film layer is prepared by a cyclic voltammetric electrodeposition method; the process of preparing the iridium oxide film layer by the cyclic voltammetric electrodeposition method is: dissolving an iridium source in an acid, adjusting the pH value to 9-11, obtaining a deposition solution, adding boric acid to the deposition solution to obtain a mixed solution, adding doped diamond particles to the mixed solution to obtain an electrolyte, aging and hydrolyzing the electrolyte, and then using the substrate as an anode to perform cyclic voltammetric electrodeposition to obtain the iridium oxide film layer; The doping element in the doped diamond particles is selected from at least one of boron, nitrogen, phosphorus and lithium; In the mixed solution, the mass ratio of iridium source to boric acid is 1g:4-50mg; The mass ratio of the doped diamond particles to the mixed liquid is 0.05-10:1000.
2. The iridium oxide-doped diamond double-layer electrode according to claim 1, characterized in that: The substrate is selected from one of the metals nickel, niobium, tantalum, zirconium, copper, titanium, cobalt, tungsten, molybdenum, chromium, iron or one of their alloys; or the substrate is selected from one of the ceramics Al2O3, ZrO2, SiC, Si3N4, BN, B4C, AlN, TiB2, TiN, WC, Cr7C3, Ti2GeC, Ti2AlC and Ti2AlN, Ti3SiC2, Ti3GeC2, Ti3AlC2, Ti4AlC3, BaPO3; or the substrate is selected from one of the composite materials composed of the above metals and ceramics, or the substrate is selected from diamond or Si; The base shape is at least one of powder, granular, cylindrical, cylindrical, and flat; The substrate structure is selected from at least one of a three-dimensional continuous network structure, a two-dimensional continuous mesh structure and a two-dimensional closed flat plate structure.
3. The iridium oxide-doped diamond double-layer electrode according to claim 1, characterized in that: The volume fraction of the doped diamond particles in the iridium oxide film layer is 0.1%-20%; the iridium oxide film matrix contains boron doping, and the molar ratio of iridium to boron is 1:1-3; The doping element in the doped diamond film layer is selected from at least one of boron, nitrogen and phosphorus, and the doping method is selected from one or more combinations of constant doping, multi-layer variable doping and gradient doping; the mass fraction of the doping element in the doped diamond film layer is 2‰-10‰; the doped diamond film layer forms a full coating, a semi-coating or a selective coating on the surface of the iridium oxide film layer; The doping mode of the doping elements in the doped diamond particles is one or more combinations of constant doping, multi-layer variable doping, and gradient doping; the mass fraction of the doping elements in the doped diamond particles is 2‰-10‰.
4. An iridium oxide-doped diamond double-layer electrode according to any one of claims 1 to 3, characterized in that: The iridium oxide-doped diamond double-film electrode comprises a substrate and an electrode working layer arranged on the surface of the substrate. The electrode working layer is a double-layer film structure, which comprises an iridium oxide film layer and a doped diamond film layer from bottom to top.
5. An iridium oxide-doped diamond double-layer electrode according to any one of claims 1 to 3, characterized in that: The iridium oxide-doped diamond double-film electrode comprises a substrate and an electrode working layer arranged on the surface of the substrate. The electrode working layer is a double-layer film structure, which comprises a doped diamond film layer and an iridium oxide film layer from bottom to top.
6. The method for preparing an iridium oxide-doped diamond double-layer electrode according to claim 4, characterized in that: First, an iridium oxide film layer is prepared on the surface of a substrate by cyclic voltammetry electrodeposition, and then a doped diamond film layer is prepared on the surface of the substrate containing the iridium oxide film layer by chemical vapor deposition; The process of preparing the iridium oxide film layer by the cyclic voltammetry electrodeposition method is as follows: dissolving an iridium source in an acid, adjusting the pH value to 9-11 to obtain a deposition solution, adding boric acid to the deposition solution to obtain a mixed solution, adding doped diamond particles to the mixed solution to obtain an electrolyte, aging and hydrolyzing the electrolyte, and then using the substrate as an anode to perform cyclic voltammetry electrodeposition to obtain the iridium oxide film layer; The mass ratio of the doped diamond particles to the mixed liquid is 0.05-10:1000; In the mixed solution, the mass ratio of iridium source to boric acid is 1g:4-50mg; The process of preparing a doped diamond film layer by chemical vapor deposition is as follows: placing the obtained substrate material in a chemical deposition furnace, introducing a gas with a mass flow ratio of hydrogen:methane:doping gas source = 100:(1-5):(01.-2.5), a growth pressure of 2-5Kpa, a growth temperature of 600-950°C, and a growth number of 1-4 times. After each growth, the substrate is taken out, and the positive and negative sides are replaced before continuing the growth. The single growth time is 1-20 hours, and the doping gas source is selected from at least one of ammonia, phosphine, and borane.
7. The method for preparing an iridium oxide-doped diamond double-layer electrode according to claim 6, characterized in that: The iridium source is selected from at least one of IrCl3, K2IrCl6, K3IrCl6, IrCl4, and H2IrCl6; The acid is selected from one of oxalic acid, hydrochloric acid and nitric acid; At least one of potassium carbonate, potassium bicarbonate and potassium hydroxide is used to adjust the pH value to 9-11; in the deposition solution, the molar ratio of iridium to hydrogen ion is 0.5-4:10; In the mixed solution, the mass ratio of iridium source to boric acid is 1g:4-50mg; The mass ratio of the doped diamond particles to the mixed liquid is 0.05-10:1000; The electrolyte aging and hydrolysis time is ≥ 1h; The electrodeposition time is 0.5-2h; During cyclic voltammetry electrodeposition, a graphite electrode or a Ti electrode is used as the counter electrode, and a saturated calomel electrode is used as the reference electrode; The parameters of the cyclic voltammetry electrodeposition are: a voltage lower limit of -1.5 to 0.2 V, a voltage upper limit of 0 to 1.8 V, a scanning rate of 5 to 500 mV / s, and a scanning number of 10 to 500 r.
8. The method for preparing an iridium oxide-doped diamond double-layer electrode according to claim 5, characterized in that: First, nano-diamond seed crystals are planted on the surface of the substrate, then a doped diamond film layer is prepared by chemical vapor deposition on the surface of the substrate planted with the nano-diamond seed crystals, and then an iridium oxide film layer is prepared by electrodeposition on the surface of the substrate containing the doped diamond film layer; The process of preparing a doped diamond film layer by chemical vapor deposition is as follows: placing a substrate planted with nano-diamond seed crystals in a chemical deposition furnace, introducing a gas with a mass flow ratio of hydrogen:methane:doping gas source=100:(1-5):(01.-2.5), a growth pressure of 2-5Kpa, a growth temperature of 600-950°C, and a growth frequency of 1-4 times. After each growth, the substrate is taken out, and the positive and negative sides are replaced before continuing the growth. The single growth time is 1-20 hours, and the doping gas source is selected from at least one of ammonia, phosphine, and borane. The process of preparing the iridium oxide film layer by the electrodeposition method is as follows: dissolving an iridium source in an acid, adjusting the pH value to 9-11 to obtain a deposition solution, adding boric acid to the deposition solution to obtain a mixed solution, adding doped diamond particles to the mixed solution to obtain an electrolyte, aging and hydrolyzing the electrolyte, and then using the substrate as an anode to perform cyclic voltammetry electrodeposition to obtain the iridium oxide film layer; In the deposition solution, the molar ratio of iridium to hydrogen ions is (0.5-4):10; In the mixed solution, the mass ratio of the iridium source to the boric acid is 1 g:4-50 mg.
9. The method for preparing an iridium oxide-doped diamond double-layer electrode according to claim 8, characterized in that: The process of planting nano-diamond seed crystals on the surface of the substrate is as follows: vertically suspending the substrate containing the ruthenium oxide active film layer and immersing it in a suspension containing nano-diamond seed crystals, ultrasonically vibrating for ≥15 minutes, and finally washing and drying with alcohol. The nano-diamond seed crystals have a particle size of 5-20nm, and the mass concentration of the nano-diamond seed crystals in the suspension is 1-5%; The iridium source is selected from at least one of IrCl3, K2IrCl6, K3IrCl6, IrCl4, and H2IrCl6; The acid is selected from one of oxalic acid, hydrochloric acid and nitric acid; Using at least one of potassium carbonate, potassium bicarbonate and potassium hydroxide to adjust the pH value to 9-11; In the deposition solution, the molar ratio of iridium to hydrogen ions is (0.5-4):10; In the mixed solution, the mass ratio of iridium source to boric acid is 1g:4-50mg; The mass ratio of the doped diamond particles to the mixed liquid is 0.05-100:1000; The electrolyte aging and hydrolysis time is ≥ 1h; The electrodeposition time is 0.5-2h; During cyclic voltammetry electrodeposition, a graphite electrode or a Ti electrode is used as the counter electrode, and a saturated calomel electrode is used as the reference electrode; The parameters of the cyclic voltammetry electrodeposition are: a voltage lower limit of -1.5 to 0.2 V, a voltage upper limit of 0 to 1.8 V, a scanning rate of 5 to 500 mV / s, and a scanning number of 10 to 500 r.
10. Use of an iridium oxide-doped diamond double-film electrode according to any one of claims 1 to 5 or an electrode prepared by the method for preparing an iridium oxide-doped diamond double-film electrode according to any one of claims 6 to 9, characterized in that: The doped diamond-iridium oxide coupling electrode is applied to the fields of electrochemical synthesis, electrochemical sewage purification, electrochemical detection and electrochemical biosensor.
Citation Information
Patent Citations
Electrode for electrolysis having durability
JP1997279398A
Method for producing electrode for electrolysis
JP2005320614A